Effect of Curcuma Longa Rhizome Extract on Fasting Blood Sugar Levels and HbA1C in Type 2 Diabetes Mellitus: A Meta-Analysis - Fatony, Riska Fajar; Tamtomo, Didik Gunawan; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Diabetes mellitus (DM) is a metabolic disease that is developing into a serious global problem. Diabetes mellitus is characterized by an increase in blood levels that are more than the normal reference. In type 2 DM generally occurs due to reduced insulin secretion and sensitivity over time. Control of blood sugar levels can improve the patient's quality of life. This study aimed to analyze the effect of curcuma longa rhizome extract on fasting blood sugar levels and HbA1C in patients with type 2 diabetes.Subjects and Method: This was a meta-analysis of a number of randomized controlled trials. The articles were obtained from PubMed, Google Scholar, Springerlink, BMJ, and Sciencedirect databases, published from 2010-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. P: Type 2 diabetes patients, I: Curcuma longa rhizome extract, C: Placebo, and O: Fasting blood sugar levels and HbA1C. The keywords to find articles are as follows: "Curcuma longa", OR "Curcumin" OR "Tumeric" OR "Curcuma" AND "Fasting blood glucose" AND "HbA1C" OR "Glicemic" OR "Diabetes Mellitus" AND "Randomized Controll Trials". Articles were collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 14 articles were reviewed in this study. Meta-analysis of 12 articles showed that the curcuma longa rhizome extract reduced fasting blood sugar levels (Standardized Mean Difference= -0.48; 95% CI= -0.61 to -0.34; p <0.001). The meta-analysis of 11 articles showed that administration of curcuma longa rhizome extract decreased HbA1C levels (Standardized Mean Difference= -0.40; 95% CI= -0.59 to -0.20; p <0.001). This meta-analysis combines primary studies from Iran, Japan, Thailand, China, Mexico, Brazil, and AustraliaConclusion: Curcuma longa rhizome extract reduces fasting blood sugar and HbA1C levels in patients with type 2 diabetes.Keywords: Curcuma longa, Fasting blood sugar levels, HbA1C, diabetes mellitus type 2, randomized controlled trialCorrespondence: Riska Fajar Fatony. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: respatieka10@gmail.com.Indonesian Journal of Medicine (2021), 06(02): 119-134https://doi.org/10.26911/theijmed.2021.06.02.01